Journal of Mammary Gland Biology and Neoplasia - Sumbalova Koledova, Zuzana; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Journal of Mammary Gland Biology and Neoplasia is the leading journal in the field of mammary gland biology that provides researchers within and outside the field with an integrated source of information pertaining to the development, function, and pathology of the mammary gland. The journal publishes a combination of peer-reviewed original research, reviews, commentaries, and perspectives covering all topics related to the field of mammary gland biology, including mammary development, breast cancer biology, lactation, and milk composition and quality. The environmental, endocrine, nutritional, and molecular factors regulating these processes are covered, including from a comparative biology perspective.
Keywords: Oncology; Cancer; Oncology; Cancer Biology